2016
DOI: 10.1002/chem.201603436
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Coupling of Organolithium with Ethers or Aryl Ammonium Salts by C−O or C−N Bond Cleavage

Abstract: Various aryl-, alkenyl-, and/or alkyllithium species reacted smoothly with aryl and/or benzyl ethers with cleavage of the inert C-O bond to afford cross-coupled products, catalyzed by commercially available [Ni(cod) ] (cod=1,5-cyclooctadiene) catalysts with N-heterocyclic carbene (NHC) ligands. Furthermore, the coupling reaction between the aryllithium compounds and aryl ammonium salts proceeded under mild conditions with C-N bond cleavage in the presence of a [Pd(PPh ) Cl ] catalyst. These methods enable sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 121 publications
0
49
1
Order By: Relevance
“…However, this breakthrough was overlooked for decades, until quite recently. After the development of improved conditions, ArOR can now be used as a coupling partner in several types of transition metal (TM)-catalyzed cross-couplings and related transformations, such as Suzuki-Miyaura-type (B), [24][25][26][27][28][29][30][31] Negishi-type (Zn or Al), [32][33][34][35][36] Murahashi-type (Li), [37][38][39][40] and other reactions. [41][42][43][44][45][46][47][48][49][50] As a continuation of our work in this area, we reported in 2012 the first ethereal Negishi-type coupling of aryl alkyl ether 36) (Chart 1(1)) and in 2016 we reported a systematic examination of ethereal Murahashi-type reaction 37) (Chart 1(2)).…”
mentioning
confidence: 99%
“…However, this breakthrough was overlooked for decades, until quite recently. After the development of improved conditions, ArOR can now be used as a coupling partner in several types of transition metal (TM)-catalyzed cross-couplings and related transformations, such as Suzuki-Miyaura-type (B), [24][25][26][27][28][29][30][31] Negishi-type (Zn or Al), [32][33][34][35][36] Murahashi-type (Li), [37][38][39][40] and other reactions. [41][42][43][44][45][46][47][48][49][50] As a continuation of our work in this area, we reported in 2012 the first ethereal Negishi-type coupling of aryl alkyl ether 36) (Chart 1(1)) and in 2016 we reported a systematic examination of ethereal Murahashi-type reaction 37) (Chart 1(2)).…”
mentioning
confidence: 99%
“…Since the pioneering work by Wenkert et al. in 1988, several protocols for Ni or Pd‐catalyzed cross‐coupling reactions of ammonium salts via C−N bond cleavage have been reported . We recently reported Stille (Sn) and Murahashi (Li) couplings via C−N bond cleavage.…”
Section: Methodsmentioning
confidence: 99%
“…Sincet he pioneering work by Wenkert et al in 1988, [10a] several protocols for Ni or Pd-catalyzed cross-coupling reactions of ammonium salts via CÀNb ond cleavage have been reported. [10][11][12][13][14][15][16] We recently reported Stille (Sn) [13] and Murahashi (Li) [14] couplings via CÀN bond cleavage. Wes ubsequently found that aryl aluminum reagents could react efficientlywith aryl ammoniums in the presence of aN ic atalyst.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A tactic is to convert arylamines to triazenes or arylammonium salts to weaken the C−N bonds before cleavage. We and other groups have performed some transition‐metal catalyzed cross‐coupling reactions using aryltrimethylammonium salts as the electrophilic partners in the past few years …”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 99%